"Considering the sickness of my children, my heart was exceedingly sunk": fatherhood and children's health in colonial New England, 1660–1785 - LeDoux, Libby, author; Little, Ann, advisor; Orsi, Jared, committee member; Hutchins, Zach, committee member (Colorado State University. Libraries, 2023)
A reading of Puritan fathers' personal writings from 1660–1785 indicates a larger ethic of loving, hands-on fatherhood. When fathers wrote about their children in their personal writings, it was most often related to their children's spiritual and physical health. By providing for their children in times of physical distress, Puritan fathers participated in the private life of their families and formed intimate bonds with their children. This thesis challenges the narratives that present the distribution of household labor as divided between the public and private. It rejects the assumption that caring for children was women's work and sickrooms were women's spaces. The fathers examined in this thesis were mentally, emotionally, and physically present throughout their children's illnesses. Fathers' detailed descriptions of their children's physical health and the medicine given to them to ease their suffering makes it clear that the sickroom was not strictly a place for women. In addition to physical remedies, fathers also employed spiritual methods to cure their children in hopes of earning God's favor. Fathers had to reckon with the religious aspects of physical disease. They ruminated on the possible causes for disease, sought for religious meaning in their children's illnesses, and worried for the sanctification of their children's souls. At its core, this thesis tells the story of fathers who loved their children. It does not paint these fathers as men who cared for their children because of an internalized goal of living up to an abstract concept of ideal Puritan manhood or paternal power. A reading of these diaries does not unveil a series of emotionally distant patriarchal authoritarians. These men were hands-on fathers who deeply loved their families and wanted to protect their children at all costs.
Considering the sickness of my children, my heart was exceedingly sunk: fatherhood and children's health in colonial New England, 1660–1785
Keywords: family history; health; Puritan; fatherhood; childhood; medicine